2021
DOI: 10.3390/molecules26061717
|View full text |Cite
|
Sign up to set email alerts
|

Lupin Protein Isolate Structure Diversity in Frozen-Cast Foams: Effects of Transglutaminases and Edible Fats

Abstract: This study addresses an innovative approach to generate aerated foods with appealing texture through the utilization of lupin protein isolate (LPI) in combination with edible fats. We show the impact of transglutaminases (TGs; SB6 and commercial), glycerol (Gly), soy lecithin (Lec) and linoleic acid (LA) on the micro- and nanostructure of health promoting solid foods created from LPI and fats blends. 3-D tomographic images of LPI with TG revealed that SB6 contributed to an exceptional bubble spatial organizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Decrease in grain number and size caused by heat stress is a rather well-known assumption (Akter & Rafiqul Islam, 2017). In this study, we examined the impact of the prolonged heat and drought and cool climate on the components of wheat grain such as, protein and starch, grain shape, and cross-sectional area of the grain by X-ray tomography (Ceresino et al, 2020(Ceresino et al, , 2021. Unfortunately, we were not able to differentiate gluten protein and starch components in the grain due the lack of contrast between these components.…”
Section: Wheat Grain Morphology By Xray Tomographymentioning
confidence: 99%
“…Decrease in grain number and size caused by heat stress is a rather well-known assumption (Akter & Rafiqul Islam, 2017). In this study, we examined the impact of the prolonged heat and drought and cool climate on the components of wheat grain such as, protein and starch, grain shape, and cross-sectional area of the grain by X-ray tomography (Ceresino et al, 2020(Ceresino et al, , 2021. Unfortunately, we were not able to differentiate gluten protein and starch components in the grain due the lack of contrast between these components.…”
Section: Wheat Grain Morphology By Xray Tomographymentioning
confidence: 99%
“…In a similar study, Ceresino et al [32] studied the impact of transglutaminases (TGs; SB6 and commercial), glycerol (Gly), soy lecithin (Lec) and linoleic acid (LA) on the microand nanostructure of solid foods for the creation of foams from LPI and fat blends that could be used to make aerated foods with an appealing texture. As in the previous study, 3-D tomographic images of LPI with TG revealed that SB6 contributed to an exceptional bubble spatial organization.…”
Section: Gliadin and Lupinmentioning
confidence: 99%